Health Care Student Knowledge and Willingness to Work in Infectious Disease Outbreaks. (19th June 2017) - Patel, Rima; Wattamwar, Kapil; Kanduri, Jaya; Nahass, Meghan; Yoon, Jennifer; Oh, Justin; Shukla, Parth; Lacy, Clifton R.
Abstract: Objective: Health care workers are critical first responders. Understanding which factors motivate their willingness to work (WTW) during infectious disease outbreaks may guide improvements in preparedness. The perspective of health care students, the future workforce, remains largely unexplored. This study compared factors influencing WTW among medical, nursing, and pharmacy students. Methods: A printed survey was administered to 631 medical, nursing, and pharmacy students. The questionnaire elicited information regarding prior disaster training, disease-related knowledge, and WTW in the setting of infectious diseases with contact or respiratory transmission. Results: Analyses of the 579 respondents (92% response rate) demonstrated that students were less fearful for their health and more willing to work during outbreaks with contact transmission than during those with respiratory transmission. Medical students were the most fearful for their health, but they demonstrated the greatest WTW, followed by nursing students, and then pharmacy students. Medical students were also the most knowledgeable about infectious diseases. Prior disaster training was associated with greater WTW. Conclusions: Extent of disease-related knowledge and prior disaster training appear to influence WTW. Our findings, taken in the context of a remarkable underemphasis on disaster preparedness in health care curricula, call for a broader incorporation of disaster training to improve the WTW of health care students, and, ultimately, health care workers. ( Disaster Med Public Health Preparedness . 2017;11:694–700)